Refining case management for dementia using insights from operations management. (19th August 2014) - Meijboom, Bert; Van den Bosch, Laurens; Schalk, René; Poland, Fiona
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose Providers of healthcare services face increasing performance demands in terms of cost-efficiency as well as client-centeredness. Dementia care is an illustrative example in this respect. Due to the aging society, the number of dementia clients is expected to grow significantly, which implies increasing costs. At the same time, demands in terms of coherent and high quality care for dementia clients are increasing, putting a stronger emphasis on demand-driven, responsive care and service processes. Literature shows that case management in dementia care is beneficial for persons with dementia and caregivers, but costly. Using insights from operations management a new model is developed for case management in dementia care. Design/methodology/approach To address both cost containment and customer orientation, insights from operations management, in particular front/back office configuration and modularity theory, are used to develop an innovative conceptual model for case management in dementia care. Findings This framework offers a new way of conceptualizing care provision throughout the different phases of a chronic disease process. Linking front/back office configurations and modular organizing with case management makes it possible to create a cost-effective and client-centered system of healthcare management. Originality/value A new model is developed to address both cost containment and customer orientation based on insights from operations management, in particular front/back office configuration and modularity theory.